A STUDY ON CLINICOPATHOLOGICAL PROFILE AND OUTCOME OF GASTROINTESTINAL PERFORATIONS: A PROSPECTIVE OBSERVATIONAL STUDY - SANJAY D DAKHORE; SAHAN M S; VIDHEY TIRPUDE; SHILPA PANDE; SUNIL B WANKHADE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objectives of the study are as follows: (1) To study the clinicopathological profile and outcome of gastrointestinal (GI) perforations. (2) To study the incidence, demographics, etiology, clinical features, management techniques, and factors influencing outcomes in cases of GI perforations. Methods: This was a prospective cohort study conducted in the Department of General Surgery in a tertiary care center in central India. One hundred and twenty cases of GI perforation were included in this study. Demographic data, detailed medical history, and present complaints were recorded for each patient. Clinical features were assessed by thorough physical and systemic examinations. Relevant laboratory tests, imaging, and operative findings were investigated. Management included operative interventions and postoperative analysis with documentation of complications. For statistical purpose, p<0.05 was taken as statistically significant. Results: The study observed a significant male preponderance in cases of GI perforations (M: F ratio 1:0.27). Patients’ age ranged from 18 to 86 years, with the highest incidence in those over 50 years (33.6%). Most patients were from Class IV and V socioeconomic status. Abdominal pain (100%) and vomiting (76.2%) were common symptoms. Hypertension (17.2%) and diabetes (14.7%) were prevalent comorbidities, with alcohol consumption (40.16%) as a notable risk factor. Gastroduodenal perforations were most frequent (63.93%). Common surgical interventions included modified Graham’s patch (62.3%) and appendicectomy (12.3%). Surgical site infections (20.4%) were common complications. Mortality was 11.4%, primarily due to sepsis. Conclusion: Early diagnosis and proper interventions are the cornerstone of management in cases of GI perforation. Prognosis depends on symptom duration, perforation site, peritoneal contamination, preoperative hypotension, and need for preoperative abdominal drainage. Chances of mortality increase in patients who present late after perforation.